GTPases regulating membrane dynamics - Balch, William Edward, 1949-; Der, Channing J.; Hall, A. (Alan) (Methods in enzymology ;, 2005)
GTPases that regulate the myriad of membrane fission events that facilitate the assembly and disassembly of COPII (Sar1), COPI (ARF) and clathrin coats (dynamin) involved in exocytic and endocytic trafficking pathways and mitochrondrial organization remain a major challenge for future investigations to understand membrane architecture of eukaryotic cells. This volume of MIE provides a comprehensive set of articles describing the use and application of state-of-the-art methodologies to identify and characterize these GTPases and their rapidly expanding list of regulators and effectors. Methodologies focused on biochemical, molecular and advanced imaging techniques provide a wealth of investigational tools for those currently in the field and those entering the field. Many of the methodologies are generally applicable to study of these GTPases in vitro and in vivo to elucidate function in regulation of cell proliferation and signaling in normal tissue and in disease. *Comprehensive collection of GTPases (ARF, Sar1, Dynamin) GTPases involved in vesicle coat assembly and membrane fission *Identification and characterization of GTPase GEFs, GAPs and effectors *General methodologies to study GTPase function in vitro and in vivo.